Board Of Directors’ Diversity And Effect On Strategy. A Study Of The Lebanese Banking Industry - Jacques L. Hendieh (European Scientific Journal, ESJ, 2016)
The purpose of this study was to examine the effect of the functional background diversity of boards of directors on banks’ strategy. This relationship is examined using the annual reports between 2005 and 2014 for 16 Lebanese banks. Logistic regression analysis indicates that board diversity is positively associated with the strategies adopted by banks. Implications for both strategic management and future research are discussed.